2003
DOI: 10.1016/s1525-0016(03)00242-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional targeting of dendritic cells in gene gun-mediated DNA immunization favors the induction of type 1 immune responses

Abstract: Cutaneous dendritic cells (DC) are pivotal for the elicitation of antigen-specific immune responses following gene gun-mediated biolistic transfection of the skin. We transcriptionally targeted transgene expression to DC using vectors containing the murine fascin promoter (pFascin) to control antigen production and compared the immune response elicited with conventional DNA immunization using plasmid constructs with the ubiquitously active CMV promoter (pCMV). Biolistic transfection with pFascin initiated a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 48 publications
4
55
1
Order By: Relevance
“…A similar result was obtained when the DCspecific fascin promoter was used in gene gun-mediated immunization (39). In this case the authors showed that the fascin promoter induced a Th1 immune response, whereas a constitutive CMV promoter led to a Th2 response (39). However, the CD11c promoter was ineffective compared to the CMV promoter or the keratinocyte-specific K14 promoter in another gene gun vaccination study (24).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A similar result was obtained when the DCspecific fascin promoter was used in gene gun-mediated immunization (39). In this case the authors showed that the fascin promoter induced a Th1 immune response, whereas a constitutive CMV promoter led to a Th2 response (39). However, the CD11c promoter was ineffective compared to the CMV promoter or the keratinocyte-specific K14 promoter in another gene gun vaccination study (24).…”
Section: Discussionmentioning
confidence: 55%
“…The same dectin-2 gene promoter has also been used in gene gun-mediated delivery of plasmid DNA, and in this case it also induced cellular immune responses (31). A similar result was obtained when the DCspecific fascin promoter was used in gene gun-mediated immunization (39). In this case the authors showed that the fascin promoter induced a Th1 immune response, whereas a constitutive CMV promoter led to a Th2 response (39).…”
Section: Discussionmentioning
confidence: 62%
“…22 ELISA capture Abs for murine IFN-␥ (clone R4-6A2) and IL-4 (11B11) were purchased from BD Pharmingen; Ab for murine IL-10 (JES052A5) was obtained from R&D Systems. Biotinylated detection Abs for IFN-␥ (XMG1.2) and IL-4 (BVD6-24G2) were obtained from BD Pharmingen, and Ab to IL-10 (BAF417) was obtained from R&D Systems.…”
Section: Cytokine Assaysmentioning
confidence: 99%
“…Therefore, the cellular localization of the expressed Ag might influence both magnitude as well as quality of responses (14 -17). As a consequence from this apparently prominent role of DC in DNA vaccination, several groups used DC-specific promoters (17,18) to enhance DNA vaccination efficacy by specifically targeting DC. However, most DNA vaccination studies investigating these types of vaccines either lack in vivo data or were based on i.m.…”
mentioning
confidence: 99%